Power quality stabilization system for grid connected large-scale solar power system - Kalal, Vijay Kumar; Byalihal, Shankarlingappa Channappa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper presents solution to power quality issues when integrating a 1.5 MW photovoltaic array (PVA) with a unified power quality conditioner (UPQC) into the power grid. A modified unit vector template control scheme is used to generate a reference load voltage signal, and a synchronous reference frame (SRF) is created using a low-pass filter to control UPQC. Furthermore, the PVA is interfaced with the grid through a common DC link of shunt and series converters. The series converter mitigates power quality problems allied with the grid side, such as 3rd, 5th, and 7th harmonics, voltage sag, and voltage swell, by introducing signals in phase and out of phase voltage, respectively, at the point of common coupling (PCC). The shunt converter mitigates nonlinear load current harmonics and compensates for reactive power using SRF. The suggested methodology is implemented using MATLAB Simulink with both linear and nonlinear loads under different power quality conditions. Total harmonic distortions are maintained below 5% at PCC, as per IEEE-519 standards.